MANAJEMEN PENGELOLAAN ARTIKEL PADA INTERNATIONAL CONFERENCE ON ADVANCED COMPUTER SCIENCE AND INFORMATION SYSTEMS (ICACSIS) - Sumarsih C Purbarani; hanif wisesa; ari wibisono (Faculty of Computer Science Universitas Indonesia, 2015)
On the contribution to scientific publications, The Faculty of Computer Science Universitas Indonesia (Fasilkom UI) holds an annual international conference entitled International Conference on Advance Computer Science and Information Systems (ICACSIS). This international conference is aimed to be a platform for scientists all over the world to present their findings to other colleagues of the same interest. The process of collecting papers from these particular countries is not easy. Thus, a system that can automatically manage the paper submission process is needed. There are numerous webbased conference management systems on the Internet. Despite the basic common features, many of them offer various features that distinguish them from the others. This paper presents various features that are available in the market, analyzes the functions of features that meets the ICACSIS paper management’s requirement and integrating both the former and the later.